(untitled) (Eurasian Journal of Philology Science and Education, 2023)
The language is considered as an expression of national culture and national development, and the problems of cognitive linguistics are studied at the intersection of such sciences as ethnolinguistics, linguoculturology, psycholinguistics, and social linguistics. In this regard, recently in linguistics there has been an increasing need and interest in the study of conceptual nature as a linguistic picture of the world, which reflects the accumulated cultural, national ideas of a person about the world. The article studies and analyzes the concept of "otbasy/family" in the linguistic consciousness on the basis of two linguistic materials. Representatives that are part of the concept "otbasy/family" in English and Kazakh are interpreted according to cognitive paradigms that reveal the semantics of the concept "otbasy": 1) family is a house; 2) family is unity; 3) family ischildren; 4) family is a warm nest; 5) family is hospitality; 6) family is homeland; 7) family is a woman, 8) family is family members. In order to identify common and specific features of the concept "otbasy/family", the language material was studied on the basis of the proverbs of the Kazakh and English peoples. As a result of such a study, it became possible, on the basis of comparative studies of linguistic units, to determine the ethnic specificity of the mentality of these peoples, to reflect the linguistic features and linguistic and cultural nature, the specificity of consciousness and thinking of each nation. Key words: concept, concept "otbasy/family", linguistic consciousness, linguoculturology, cognitive linguistics.